Genetic variation in gene regulation - Pritchard, Jonathan (Henry Stewart Talks, 2015)
Expression Quantitative Trait Loci: linking genetic variation to changes in gene regulation, How do SNPs impact gene regulation, HapMap cell lines as a model system for studying expression variation, eQTL analysis, dsQTL, Histone marks, Protein-specific QTLs